Distinct Bradyrhizbium communities nodulate legumes native to temperate and tropical monsoon Australia - Stepkowski, T.; Watkin, Elizabeth; McInnes, A.; Gurda, D.; Gracz, J.; Steenkamp, E. (Elsevier, 2012)
Geographic isolation and growing climate aridity played major roles in the evolution of Australian legumes. It is likely that these two factors also impacted on the evolution of their root-nodule bacteria. To investigate this issue, we applied a multilocus sequence analysis (MLSA) approach to examine Bradyrhizobium isolates originating from temperate areas of Western Australia (WA) and the tropical monsoon area of the Northern Territory (NT). The isolates were mostly collected from the nodules of legumes belonging to tribes, genera and species endemic or native to Australia. Phylogenetic analyses of sequences for the housekeeping atpD, dnaK, glnII, gyrB, recA and 16S rRNA genes and nodulation nodAgene revealed that most isolates belonged to groups that are distinct from non-Australian Bradyrhizobium isolates, which is in line with earlier studies based on 16S rRNA gene sequence analyses. Phylogenetic analysis of the nodA data allowed identification of five major Clades among the WA and NT isolates. All WA isolates grouped in a subgroup I.1 of Clade I with strains originating from temperate eastern Australia. In contrast, the NT isolates formed part of Clades I (subgroup I.2), III (subgroup III.3), IV, V and X. Of these nodA clades, Clade I, Clade IV, Clade X presumably have an Australian origin. Overall, these data demonstrate that the impact of geographic isolation of the Australian landmass is manifested by the presence of numerous unique clusters in housekeeping and nodulation gene trees. In addition, the intrinsic climate characteristics of temperate WA and tropical-monsoon NT were responsible for the formation of distinct legume communities selecting for unrelated Bradyrhizobium groups.